Application of ABC classification, EOQ, FUZZY AHP, time series models to improve order fulfillment in a trading company of household appliances - Valdivia Seminario, Carlos (2025)
Most SMEs do not survive more than five years in the Peruvian market and one of the main reasons is the inefficient logistics administration and inventory control. This represents a serious problem because these businesses play a fundamental role in the growth of the country’s economy and trade. Therefore, this research focuses on the analysis of 4 engineering tools applied integrally to improve order fulfillment of a trading company of household appliances. This model makes use of tools such as: ABC classification, time series models, fuzzy AHP and EOQ. After model validation, it was observed that order fill rate increased from 80,40% to 95,61%, demonstrating the positive impact that could be generated for the business.